Concurrence of High Fat Diet and APOE Gene Induces Allele Specific Metabolic and Mental Stress Changes in a Mouse Model of Alzheimer’s Disease - Segev, Yifat; Livne, Adva; Mints, Meshi; Rosenblum, Kobi (Frontiers in Behavioral Neuroscience, 2016)
Aging is the main risk factor for neurodegenerative diseases, including Alzheimer’s disease (AD). However, evidence indicates that the pathological process begins long before actual cognitive or pathological symptoms are apparent. The long asymptomatic phase and complex integration between genetic, environmental and metabolic factors make it one of the most challenging diseases to understand and cure. In the present study, we asked whether an environmental factor such as high-fat (HF) diet would synergize with a genetic factor to affect the metabolic and cognitive state in the Apolipoprotein E (ApoE4) mouse model of AD. Our data suggest that a HF diet induces diabetes mellitus (DM)-like metabolism in ApoE4 mice, as well as changes in β-site amyloid precursor protein-cleaving enzyme 1 (BACE1) protein levels between the two ApoE strains. Furthermore, HF diet induces anxiety in this AD mouse model. Our results suggest that young ApoE4 carriers are prone to psychological stress and metabolic abnormalities related to AD, which can easily be triggered via HF nutrition.